2022
DOI: 10.1093/texcom/tgac011
|View full text |Cite
|
Sign up to set email alerts
|

Inattentive and hyperactive traits differentially associate with interindividual functional synchrony during video viewing in young children without ADHD

Abstract: Inattention and hyperactivity present on a spectrum and may influence the way children perceive and interact with the world. We investigated whether normative variation in inattentive and hyperactive traits was associated with differences in brain function while children watched clips from an age-appropriate television program. fMRI data and parent reports of inattention and hyperactivity traits were collected from 81 children 4–7 years of age with no parent-reported diagnoses. Data were analyzed using inter-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 76 publications
(86 reference statements)
0
1
0
Order By: Relevance
“…Naturalistic neuroscience studies employing video viewing approach have shown promising results in detecting aberrant brain functioning in affective disorders [32,33], psychosis [34,35], autism [36,37,38,39], and ADHD [40,41,42]. In individuals with ADHD inter-individual synchronization of regional activity is reduced compared to neurotypical controls during viewing a naturalistic stimulus in several brain areas, including the anterior cingulate cortex, supratemporal, occipital, and posterior parietal regions [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…Naturalistic neuroscience studies employing video viewing approach have shown promising results in detecting aberrant brain functioning in affective disorders [32,33], psychosis [34,35], autism [36,37,38,39], and ADHD [40,41,42]. In individuals with ADHD inter-individual synchronization of regional activity is reduced compared to neurotypical controls during viewing a naturalistic stimulus in several brain areas, including the anterior cingulate cortex, supratemporal, occipital, and posterior parietal regions [40,41].…”
Section: Introductionmentioning
confidence: 99%